Inovação responsável: expansão de um modelo teórico-metodológico com base na mobilidade inteligente - Silva, Leisianny Mayara Costa (2025)
The overall objective of this thesis was to analyze the contributions and practical context of RI in the SM context, proposing a theoretical-methodological model capable of diagnosing this phenomenon. Drawing on the contributions of studies related to RI in the SM context, the first article sought to analyze and advance the epistemological field of RI praxis, proposing Experimentation as a new dimension. The second article systematically reviewed and determined the context of practices in this context, suggesting a research agenda. Moving into the empirical phase, the third article investigated RI in SM with institutions operating in this context, bringing together possible revisions to the previous theoretical analyses. The fourth and final article, together with experts, evaluated the categories and subcategories of RI in SM and applied the findings to the proposed model, testing it empirically. The methodology adopted followed the principles of Design Science Research (DSR), integrating theoretical and empirical approaches, using a mixed methodology and methodological triangulation. A Systematic Literature Review (SLR) based on PRISMA (2020) was conducted using the following databases: Scopus, Ebsco, Web of Science, Gale, JSTOR, and Google Scholar. The empirical scenario involved: seven institutions of the Federal Government's Mover Program; 44 experts in innovation and urban mobility; and one SM company. The theoretical findings point to Experimentation as an integral dimension of the other dimensions in RI, reinforcing the importance of laboratory processes in addressing uncertainty and allowing citizens and professionals to critically examine the dynamics and trajectories of innovation. RI practices in SM were configured through six axes: Technological, Social, Eco-sustainable, Economic, Spatial, and Organizational, with guidelines for socio-ethical values and stakeholder engagement. The axes were established in components and application indicators, proposing a framework for RI practices in SM. The empirical findings validated the importance of the identified axes, adding a new one: Criticality of Innovation, as well as new perspectives and a proposed conceptualization. Correlation and regression analyses demonstrated that the formative weights were significant; the proposed model involved reflective and formative measures, in addition to the Degree of Responsible Innovation (DRI) equation. Finally, the developed artifact proved heuristically useful in analyzing the responsible landscape of urban innovations, with future potential for instrumentalization.